Design of a prototype mobile application interface for efficient accessing of electronic laboratory results by health clinicians - Chigudu, Kumbirai (Department of Computer Science, 2019)
in order for clinicians to make informed medical decisions and prescribe the correct medication within a limited specified time. Since no further informed action can be taken on the patient until the laboratory report reaches the clinician, the delivery of the report to the clinician becomes a critical path in the value chain of the laboratory testing process. The National Health Laboratory Service (NHLS) currently delivers lab results in three ways: via a physical paper report, and electronically through a web application. The third alternative is for short and high-priority test results, like human immunodeficiency virus (HIV) and tuberculosis (TB), that are delivered via short message service (SMS) printers in remote rural clinics. However, despite its inefficiencies, the paper report remains the most commonly used method. As turnaround times for basic and critical laboratory tests remain a great challenge for NHLS to meet the specified targets; there is need to shift method of final delivery from paper to a paperless secured electronic result delivery system. Accordingly, the recently-implemented centralised TrakCare Lab laboratory information system (LIS) makes provision for delivery of electronic results via a web application, ‘TrakCarewebview’. However, the uptake of TrakCarewebview has been very low due to the cumbersomeness of the application; this web application takes users through nine steps to obtain the results and is not designed for mobile devices. In addition, its access in remote rural health care facilities is a great challenge because of lack of supportive infrastructure. There is therefore an obvious gap and considerable potential in diagnostic result delivery system that calls for an immediate action to design and development of a less complex, cost effective and usable mobile application, for electronic delivery of laboratory results. After obtaining research ethics clearance approval from the University’s Faculty of Science Research Ethics Committee a research was sanctioned. A survey of public sector clinicians across South Africa indicated that 98% have access to the internet through smartphones, and 93% of the clinicians indicated that they would use their mobile devices to access electronic laboratory results. A significant number of clinicians believe that the use of a mobile application in health facilities will improve patient care. This belief, therefore, set a strong basis for designing and developing a mobile application for laboratory results. The study aims to design and develop a mobile application prototype that can demonstrate the capability of delivering electronic laboratory test results to clinicians on their smart devices, via a usable mobile application. The design of the mobile application prototype was driven by user-centred design (UCD) principles in order to develop an effective design. Core and critical to the process is the design step which establishes the user requirements specifications that meet the user expectations. The study substantiated the importance of the design aspect as the initial critical step in obtaining a good final product. The prototype was developed through an iterative process alternating prototype development and evaluation. The development iterations consisted of a single paper prototyping iteration followed by further two iterations using an interactive Justinmind prototyping tool. Respective to the development iterations, cognitive walk-through and heuristic principles were used to evaluate the usability of the initial prototype. The final prototype was then evaluated using the system usability scale (SUS) survey quantitative tool, which determines the effectiveness and perceived usability of the application. The application scored an average SUS score of 77, which is significantly above the average acceptable SUS score of 68. The standard SUS measurement deems 80 to be an excellent score. Yet a score below 68 is considered below average. The evaluation was conducted by the potential user group which was involved in the initial design process. The ability of the interactive prototyping tool (Justinmind) to mimic the actual final product offered end users a feel of the actual product thus giving the outcome of the evaluation a strong basis to develop the actual product.